Anti-terror reforms - A snapshot of the situation in Saudi Arabia - Iris Glosemeyer; Volker Perthes (Stiftung Wissenschaft und Politik (SWP), 2004)
The bombings in Riyadh that shook Saudi Arabia in early November are unlikely to be the last such attacks, for extremist Islamist groups which are prepared to perpetrate acts of violence have more supporters in the kingdom than the government has been prepared to admit to itself or to others. Since 11 September 2001, Saudi Arabia has come under closer scrutiny in the international arena. Simultaneously, people within the country have started taking a critical look at the situation there, and it has become clear to the Saudi leadership that structural and policy changes are essential if the kingdom's survival is to be guaranteed. Moreover, the Saudi leadership is aware that its relations with its most important foreign partner, the United States, are precarious. Meanwhile, the pressure for reform, prompted by long-term, structural causes, has been stepped up by substantial geostrategic changes. After years of stagnation, the process of domestic reform, faltering since 1993, has clicked into gear once again. At the same time, the internal balance of power has shifted quite dramatically over the past decade.(SWP Comments / SWP)
Keywords: 320